Larval rearing and juvenile production of tropical black sea urchin, Diadema setosum (Leske, 1778) - Abdul Wahab, Mohammad Sarifudin (2018)
Long-spined black sea urchin Diadema setosum were successfully cultured within 35 days in closed culture system at a culture temperature of 28ºC. Complete observations of their physical characteristics and skeleton structure were done to determine normal and healthy larvae using this culture method. Trials on environmental effects discovered the critical range for high survival of this sea urchin larva. On salinity, it was shown that D. setosum larvae could not survive and develop when salinity is less than 28 or more than 37 PSU. The best salinity was at 31 PSU. Moreover, fertilization success decreased with increasing or decreasing salinities. The critical tolerance temperature for embryonic development was 16 and 34°C for the minimum and maximum levels, respectively. Among these, 28°C was the best temperature for growth and development rates in all larval stages. Optimization on culture methods was done by determining the optimal food concentrations, larval densities, and food types. Food concentration showed a trade-off relation between arm length and stomach size of the larvae with a value of -0.955 which was likely due to evolution plasticity of feeding structures. The best density for survival and development of larvae culture was 1 larvae/m, leading to a survival of 67.33%. The best microalgae for D. setosum was Chaetoceros calcitrans, leading to metamorphosis after 35 days, followed by mixed algae culture (C. calcitrans and Isochrysis galbana) and lastly Isochrysis galbana. All larvae cultured with Nannochloropsis sp. died before reaching the late 4-arm stage. Addition of coralline red algae induces highest percentange settlement of D. setosum as compared other micro algae. This indicates that potent inducing substances were sufficiently present in red algae. The use of biofilm did not improve the metamorphosis rate (2-5%) compared to the control. In summary, findings from this study can be useful to understanding the life cycle of this sea urchin. Investigations of other environmental factors, such as pH, alkalinity and turbulence, would likely also help customize optimum conditions for culturing the sea urchin in closed or open culture systems. Such information may help the farmer to better develop aquaculture systems for sea urchin culture.